Kontribusi Pendapatan Usahatani Bunga Pacar Air terhadap Total Pendapatan Rumah Tangga Petani di Desa Angantaka Kecamatan Abiansemal Kabupaten Badung (Jurnal Agribisnis dan Agrowisata, 2025)
Contribution of Rose Balsam Flower Farming to Total Farmer Household Income in Angantaka Village, Abiansemal District, Badung Regency. Rose blosom flower is a herbaceous plant with fibrous roots, wet stems, soft, round, branched, yellowish green in color. The rose blosom flower is used as a means of prayer by Hindu’s in Bali and not least is also used to decorate things.This study aims to determine the income of rose blosom flower farming and calculate the contribution of farming income to the total income of farmer households in Angantaka Village. Sampling technique using stratified random technique. The sample in this study was determined by grouping respondents according to the area of ​​arable land. The methods used to obtain data in this study were surveys, documentation, and in-depth interviews. Analysis of the data used is the analysis of farm income.The results of this study indicate that the average income of rose blosom flower farming in three growing seasons is IDR 13,173,049. The contribution of rose blosom flower farming income to the total household income of farmers in Angantaka Village is 33%, which is included in the low category.Suggestions that need to be considered are rose blosom flower farmers can take advantage of the advantages of rose blosom flower farming which is not complicated and production costs are not high so that farmers have more time and can share capital for farming other commodities so that it will provide a high contribution to farmer household income.
Keywords: contribution; income; rose balsam flowers; farming; farmers